Arbitration as A Choice of Forum in Dispute Resolution Regarding Deed of Agreement - Novela Christine; Mohamad Fajri Mekka Putra (LEGAL BRIEF, 2022)
One of the necessary elements in an international business contract is choice of forum, which arbitration emerged in it. The research purpose is to identify the application of arbitration as choice of forum in a notary deed. The method used in this journal is juridical-normative research. Arbitration clause is necessary in a notary agreement in order that the arbitration will bind the parties. The annulment of the agreement doesn’t result in the arbitration clause being invalid, but severability principle upholds the enforcement of arbitration in a dispute settlement. By choosing arbitration as the choice of forum, the parties are free in selecting the arbitrators, where the arbitration take place, the language used, and the law applied in arbitration. If the clause is not included, the parties could make a deed of compromise or an agreement regarding the acceptance for arbitration in a dispute settlement after the dispute arises.